January Effect on the Thinly Traded KLSE: Tests with Appropriate Refinements - M Nasir, Annuar; Ariff, Mohamed; Mohamad, Shamsher (1992)
Over recent years the January Effect has been documented as an anomaly on stock markets around the world. The January regularity refers to the phenomenon that security returns in early January are higher than in any other period of the year. The pesence of the January Regularity on the Kuala Lumpur Stock Exchange (KLSE) has been established. However, this study investigates further the possible explanations, taking into consideration the returns on stocks rather than indices, contml for thinness of trading and the association of the regularity with size effects. The evidence indicates that returns on 298 stocks traded in KSLE do exhibit the January seasonality, and the average returns net of cost for January are 1. 75 per cent. However, these net average returns are not adjusted for 1isk, therefore it is difficult to confirm the valuational efficiency of the regularity. In contrast to the documented evidence in developed securities markets, the size effect cannot rationalise the regularity in the developing Kuala Lumpur Stock Excrhange. The possibility of the thinness of trading as a factor that could partially eXplain the regularity is supporte